(untitled) (Research, Society and Development, 2022)
The physiotherapist minimizes the impacts of functionality throughout the treatment of breast cancer. It is believed that many women are unaware of the performance of this professional, causing misunderstandings about their role in the care process. This study investigated the perception of women with breast cancer about the importance of the physiotherapist’s performance in comprehensive care during treatment. A cross-sectional and qualitative study was carried out by means of a focus group. The following categories were identified: Comprehensive care and Vision of the role of the physiotherapist. These were examined through Bardin’s content analysis. The results revealed that women know and recognize the importance of the role of this professional. The highlight on the physio therapeutic approach in breast cancer was concluded, at all levels of care, becoming essential in the care process. It is necessary to advance the discussion of the physiotherapist’s role, from the patients’ perspective, aiming at improving health planning and management and decision making during prevention, diagnosis, maintenance and rehabilitation, reaffirming the role of this professional in the process care.